How to make an efficient and robust molecular catalyst for water oxidation. (18th July 2017) - Garrido-Barros, Pablo; Gimbert-Suriñach, Carolina; Matheu, Roc; Sala, Xavier; Llobet, Antoni
Abstract : The key factors to design an efficient and rugged molecular water oxidation catalyst (Mol-WOC) are reviewed and discussed. Abstract : Energy has been a central subject for human development from Homo erectus to date. The massive use of fossil fuels during the last 50 years has generated a large CO2 concentration in the atmosphere that has led to the so-called global warming. It is very urgent to come up with C-neutral energy schemes to be able to preserve Planet Earth for future generations to come and still preserve our modern societies' life style. One of the potential solutions is water splitting with sunlight ( hν -WS) that is also associated with "artificial photosynthesis", since its working mode consists of light capture followed by water oxidation and proton reduction processes. The hydrogen fuel generated in this way is named as "solar fuel". For this set of reactions, the catalytic oxidation of water to dioxygen is one of the crucial processes that need to be understood and mastered in order to build up potential devices based on hν -WS. This tutorial describes the different important aspects that need to be considered to come up with efficient and oxidatively robust molecular water oxidation catalysts (Mol-WOCs). It is based on our own previous work and completed with essential contributions from other active groups in the field. We mainly aim at describing how the ligands can influence the properties of the Mol-WOCs and showing a few key examples that overall provide a complete view of today's understanding in this field.